Childhood Pneumonectomies: Two Decades' Experience of a Referral Center - Yalcin, Sule; Ciftci, Arbay; Karnak, Ibrahim; Ekinci, Saniye; Tanyel, Feridun Cahit; Şenocak, Mehmet (European Journal of Pediatric Surgery, 2013)
Purpose We aimed to review the pre- and postoperative characteristics of children undergoing pneumonectomy, with special emphasis on the management of surgical complications, in comparison with the current literature findings.Patients and Methods A total of 20 patients who underwent pneumonectomy for various etiologies from 1988 to 2011 were investigated retrospectively with respect to the presenting findings, preoperative evaluation, surgical information, postoperative follow-up, and outcome.Results A total of 11 girls and 9 boys with a median age of 8 years (0.5–17 years) presented with symptoms of productive cough (n = 9), recurrent chest infections (n = 9), nonproductive cough (n = 1), respiratory distress (n = 1) with a median duration of 2 years (0.16 to 12 years). Medical histories revealed chest infection (n = 11), foreign body aspiration (n = 3), aspiration pneumonia (n = 2), tuberculosis (n = 2), caustic aspiration (n = 1), and congenital lung pathology (n = 1). Clinical evaluation provided diagnoses of bronchiectasis (n = 16), total atelectasis (n = 2), bronchopleural fistula (BPF) (n = 1), and cystic lung disease (n = 1). Pneumonectomy was performed on the right in 6 and left in 14 of the cases. Pericardial (n = 1) and esophageal (n = 1) laceration were the perioperative (11.1%), massive hemorrhage (n = 1) and chylothorax (n = 1) the postoperative (11.1%), and scoliosis (n = 1) and BPF (n = 1) the long-term (11.1%) complications. Pathological evaluation revealed bronchiectasis (n = 14), consisting of three cases with additional sign of foreign body, chronic inflammation (n = 4), atelectasis with fibrous pleural thickening (n = 1), and congenital pulmonary lymphangiectasia (n = 1). A total of 14 cases were free of symptoms and 5 had significant improvement in general condition during the follow-up, for a median duration of 2 years (1 to 10). The one with the diagnosis of Becker muscular dystrophy died 2 years after pneumonectomy because of respiratory failure.Conclusions Correct selection of indications, careful preoperative preparation with eradication of infection, meticulous performance of surgical and anesthetic techniques, early detection and management of complications, and long-term follow-up including pulmonary rehabilitation are essential parameters to reduce morbidity and mortality rates in childhood pneumonectomy. Better compensatory lung growth and improvement in development after the operation will facilitate better health and improved life quality in children.
Keywords: pneumonectomy; children; etiology; complication; outcome